Serum Zinc Level in Patients with Heart Failure - Al-Hamwandi, Adnan M; Al-Dalla, Fakhri j; Mohammed, Hatem H; AL-Baldawi, Kadhim H.; AL-Baldawi, Kadhim H.; Diyaiy, Muna A (AL-Kindy College Medical Journal, 2006)
Background: Zinc is involved in a variety ofmetabolic processes and it has a well knownantioxidant activity, so the measurement of its serumlevel can have a special value in several diseases.Objectives: The study is designed to determine theserum zinc level in heart failure patients and tocompare it with that of healthy individuals and tostudy the significance of the results obtained.Methods: Atomic absorption spectrometertechnique was used to determine serum zinc level infifty heart failure patients and fifty healthy individualswho were age and sex matched.Results: The mean serum zinc level in healthyindividuals was about 45.5% greater than that of heartfailure patients. This difference was statisticallysignificant.Conclusion: The reduced serum zinc level in heartfailure patients could be an acceptable risk factor forthe development and/or deterioration of heart failureand therefore its correction might have a positiveeffect on management and prognosis of such patients